'Glocalisation' of Music Streaming within and across Europe - Will Page; Chris Dalla Riva (London School of Economics and Political Science (LSE), European Institute, 2023)
This EIQ paper was inspired by the headline 'British artists in a historic clean sweep of 2022's Official Top 10 singles'. British artists accounted for all the Top Ten of the end-of-year singles chart of 2022 - for the first time since the charts were published over 50 years ago. A quick glance across the continent uncovered a similarly intriguing trend. Many of the top ten acts in Germany were German, many in Italy were Italian and all the top ten songs in Spain were in Spanish, although the vast majority were Latin American. These observations prompted us to ask a pertinent question: has the ubiquity of streaming increased or decreased the threat of homogenisation? As consumers are now accessing their music by global platforms (not local retailers), does this help or hinder domestic markets? Our analysis of ten European markets uncovers a phenomenon that we've termed 'glocalisation', where the majority of countries studied saw an absolute and relative increase in the domestic share of their top ten songs and artists in 2022. The impact of 'glocalisation' is as important to countries' creative industries as it is to their policy makers. Contrary to the perverse effects of globalisation where large markets often dominate small, we uncover evidence of local markets growing in their domestic identity. Finally, if local European markets are benefiting from glocalisation, spare a thought for English speaking markets who traditionally had a comparative advantage in music-exports - as they are now struggling to get their English-language repertoire heard overseas.
Keywords: 330; Creative Industries; Cultural Policy; Globalisation; Homogenisation; Diversity; Music; Media; Digitisation; Streaming; Artists; Spotify; Social Attitudes; Regulation and Europe